Understanding Statistics in the Behavioral Sciences / Study Guide to Accompany: Fourth Edition - Follette William C; Pagano Robert R (West Publishing Company, 1994)
Preface, Overview, Statistics and Scientific Method, Descriptive Statistics, Basic Mathematical and Measurement Concepts, Frequency Distributions, Measures of Central Tendency and Variability, The Normal Curves and Standard Scores, Linear Regression, Correlation, Inferential Statistics, Random Sampling and Probability, Binomial Distribution, Introduction to Hypothesis Testing Using the Sign Test, Power, Mann-Whitney U Test, Students t Test for Single Samples, Introduction to the Analysis of Variance, Multiple Comparisons, Introduction to Two-Way Analysis of Variance, Chi-Square and Other Non Parametric Tests, Review of Inferential Statistics.